Ganancia excesiva de peso materno y su asociación con pre eclampsia, Hospital Regional de Loreto de enero a junio del 2022 - Cabrera Olórtegui, Fredy Jesús (2024)
The prevalence of preeclampsia in patients is 10.24%, with 376 patients in the cases. Excessive gestational weight gain (GEP) is a risk factor for preeclampsia. Overweight or obese women had a higher risk of PE in the control group. The relationship between maternal weight and the risk of preeclampsia is progressive, increasing from 4.3% for women with BMI < 20 to 13.3% in those with BMI > 353. A study of 22,073 pregnant women at the Regional Teaching Hospital of Trujillo in 2006-2015 found 835 cases of preeclampsia. Of the 62 pregnant women with preeclampsia, 46.8% had excessive weight gain during pregnancy, while 24.2% of the 124 pregnant women who did not present preeclampsia, 24.2% had excessive weight gain during pregnancy. Excessive gestational weight gain is a risk factor that has a statistically significant relationship to an increased risk of preeclampsia